The Students' Writing Difficulties in Writing an Essay Based on Cognitive Process - Hassanudin Fatsah; Ashrafiany NA; Nonny Basalama (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2020)
The main problem of this research was “what are the students” writing difficulties in writing an essay at fourth semester of Grade E? and what factors do influence the students’ writing difficulties in writing an essay based on the cognitive process at fourth semester of grade E? The objective was aimed to identify the students’ writing difficulties in writing an essay at fourth semester of Grade E and to identify the factors do influence the students’ writing difficulties in writing an essay based on the cognitive process at the fourth semester of Grade E.The subject was the students at fourth semester grade E in 2016/2017 academic year which consists of twenty two students. This research used Qualitative Research method. The data is gathered from observation, document (students’ essay) and interview. The findings showed that there are two types of students writing difficulties in writing an essay, they are pre writing and pre-drafting. The result of result that there are nine students who difficult in pre writing and there are twelve students difficult in pre writing drafting. Pre writing difficulties like difficult in getting the topic and pre-drafting difficulties like difficult in getting topic and organizing the essay.. Key words: Writing difficulties, Writing essay, cognitive process